2018
DOI: 10.1016/j.jtcvs.2018.03.144
|View full text |Cite
|
Sign up to set email alerts
|

Low rate of reoperations after acute type A aortic dissection repair from The Nordic Consortium Registry

Abstract: Type A aortic dissection repair in low- to medium-volume centers was associated with a low reoperation rate and satisfactory midterm survival. The extent of the primary repair had no significant influence on reoperation rate or midterm survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 22 publications
6
35
0
Order By: Relevance
“…A NORCAAD report from Pan et al recently showed freedom from reoperation rates of 98% at one year and 95% at five years [8]. Other studies have shown freedom from reoperation of 82-94% at five years [85,101,102].…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A NORCAAD report from Pan et al recently showed freedom from reoperation rates of 98% at one year and 95% at five years [8]. Other studies have shown freedom from reoperation of 82-94% at five years [85,101,102].…”
Section: Complicationsmentioning
confidence: 99%
“…Conservative approaches are being increasingly challenged, and more extensive primary aortic repairs suggested, addressing associated and potential future problems of aortic dilatation (in the root, arch, proximal descending aorta, or entire thoracoabdominal aorta) that may both affect longterm survival and necessitate reinterventions. Reoperations after primary ATAAD repair are not uncommon in longterm survivors, or up to 25-30% [83,84], and mortality is at a respectable 10-20% for elective reoperations on the proximal aorta (25-31% on the distal aorta),but as high as 67% in acute settings [8,[83][84][85].…”
Section: Technical Aspects Of Surgical Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Nordic Consortium for Acute Type A Aortic Dissection (NORCAAD) published their experience with acute type A aortic dissection (ATAAD) showing that the extent of primary repair had no relationship with the reoperation rate. 1 The consortium's latest contribution from Geirsson and colleagues 2 compares the 30-day mortality and short-term survival in 153 ATAAD patients who underwent clamp-on repair (ie, standard cardiopulmonary bypass with both anastomoses done with the aortic crossclamp in place) with 981 ATAAD patients who had clamp-off/open repair (ie, circulatory arrest and an open distal anastomosis) between 2005 and 2014. The 30-day mortality and 5-year survival were 25% and 61.8% AE 4.4%, respectively, for the clamp-on group and 16% and 73% AE 1.6%, respectively, for the clamp-off cohort.…”
mentioning
confidence: 99%
“…1 Total aortic correction and arch replacement have been a matter of debate because lifesaving surgery is the top priority during emergency; a restricted aortic correction of the ascending aorta such as a hemiarch replacement saves many patients. 2,3 The current article by Zhang and colleagues 4 presents a retrospective analysis of patients with DeBakey type I dissection operated by highly experienced surgical teams. Two different contemporaneous surgical techniques, both including an uncompromised aim to perform a 1-step doit-all arch reconstruction 5 with a distal endograft, are compared.…”
mentioning
confidence: 99%